Quality of Elementary School Graduates : The Contribution of Teacher Leadership, Student Self-Regulated Learning, and School Culture - Juharni, Indra; Suyatno, Suyatno; Widodo, Widodo; Nurfirdaus, Nunu; Deprizon, Deprizon (Jurnal Kependidikan, 2023)
This research aims to analyze the factors that influence the quality of elementary school graduates. Potential contributors were examined as teacher leadership, student self-regulation, and school culture. The method used is correlational research with a quantitative approach. One hundred forty-seven elementary school teachers in Bantul Regency were given a questionnaire to assess the pre-requisites. This data was then used for a multiple linear regression analysis using the SPSS version 22. The results showed a significant influence of teacher leadership, student self-regulated learning, and school culture on the quality of graduates. Teacher leadership and student self-regulated learning were the two most important factors influencing quality. Additionally, school culture was found to have a partial, significant influence on the quality of graduates. Therefore, improving teacher leadership, student self-regulated learning, and school culture in education help upgrade graduates' quality.